TEACHER’S STRATEGIES IN TEACHING SPEAKING FOR STUDENTS WITH VISUAL IMPAIRMENT - Rani Ratna Ningsih (Institut Pendidikan Indonesia Garut, 2019)
This research aimed to analyzed the strategies used by teacher and students’ impression of the strategies used by teacher in teaching speaking for students with visual impairments. To achieve these aims, a qualitative research embracing case study was chosen. The participants of this research were eleventh grade from one of SLB-A in Garut. To analyzed the data, kayi’s (2006) categories thirteen strategies in teaching speaking. The finding reveal that there were three kinds of strategies in teaching speaking conducted by teacher; storytelling, role play and story completion. Regarding the students’ impressions, there were positive impression of the students toward English, speaking and storytelling.